Physics mathematization assessment: The nominal group technique as a context to investigate student understanding - Abdelwahab El Azzouzi; Fatiha Kaddari; Abdelrhani Elachqar (Institute of Advanced Engineering and Science, 2023)
This work has its origin in physics learning with secondary school students in Morocco. The present work focuses on the relationship between physics and mathematics as well as the source of difficulties in learning the half-life concept. To highlight our research objectives, the researchers resorted to the nominal group technique (NGT) which is used not only to identify students’ opinions about physics mathematization difficulties but also to assess the scientific education of this discipline. The results obtained showed that mathematics has an impact on Moroccan students’ understanding of the half-life concept. The results also showed that coherent and simultaneous management of physics and mathematics favors the learning of Moroccan students in both disciplines.